Decomposing Brand Loyalty: An Examination of Loyalty Subcomponents, Product Price Range, Consumer Personality, and Willingness to Pay - Gabriele Damaschi; Ali Aboueldahab; Marco D’Addario (Behavioral Sciences, 2025)
Brand loyalty is widely recognized as a key driver of consumer behavior, significantly influencing their willingness to pay more for preferred brands. This study explores the relationship between brand loyalty, its components, willingness to pay, consumer personality traits, and product price range. A tailored online survey involving participants aged 18 to 60 revealed a strong positive correlation between brand loyalty and increased willingness to pay. The findings also underscore the influence of Conscientiousness and Energy on brand loyalty, alongside the moderating effect of product price range. Specifically, habit-based loyalty dominates low-priced, routine purchases, while higher-priced decisions involve deeper cognitive-affective evaluations. These insights offer valuable guidance for enhancing customer satisfaction and optimizing brand profitability.